The pathway toward pollution mitigation in EU28 region: does hydropower growth make a difference? - Mohd Alsaleh; A.S., Abdul Rahim (Elsevier, 2022)
This research examines the impact of hydropower industry growth on carbon dioxide releases in twenty-eight nations under the European Union (EU 28) dated from 1990 to 2018. Utilizing panel fully modified ordinary least squares (FMOLS), the outcomes show that carbon dioxide releases decreased and growth in hydropower production and good governance. While fossil-fuel, economic growth, and urbanization discovered carbon dioxide releases were fluctuating. The results show carbon dioxide releases in EU28 nations can be efficiently lessened thru expanding the quantity of hydropower output in resource sustainability and security agenda. In time, it will add to discussing environmental pollution and climate change. The assessed outcomes were regards as strong as they were authenticated by the panel's dynamic ordinary least square (DOLS) and pooled ordinary least square (pooled OLS). This report endorses for EU28 nations to escalate the part of hydropower dynamics combination towards carbon dioxide release reduction. Politicians and governors under EU28 nations must increase investment in producing hydropower output to boost renewable energy sources and availability. The EU28 nation's government will be able to stress in usefulness and continuity of hydropower output and good governance to attain power assurance, sustainability, and lessened reliance on conventional oil.